A new overall nonlinear damage model for fiber metal laminates based on continuum damage mechanics. (1st February 2019) - Kashfi, M.; Majzoobi, G.H.; Bonora, N.; Iannitti, G.; Ruggiero, A.; Khademi, E.
Graphical abstract: Highlights: A new overall damage model is proposed to predict the induced damage of FML. A sensitivity analysis indicates that εcr, nm has the most effect on the FML damage. CPU time reduced by 4 times using the present model compared with layered model. Reasonable agreement between the present model and the experiment was obtained. Abstract: Fiber Metal Laminates (FMLs) are hybrid composites made of interlacing layers of thin metal and fiber reinforced layers. In this work, a new overall damage model is developed to estimate the damage of FML considering the influence of stress triaxiality. The parameters of the damage model were determined using tensile test and iterative FE optimization for each sub-layer. Moreover, the stiffness degradation test was carried out to validate the proposed model for FML plain specimen. Additionally, notched FML specimens were used to simulate the material behavior under more complicated states of stress by implementing the proposed damage model in MSC MARC commercial FE code. A reasonable agreement was obtained between the FE and the experimental results for plain and notched FML specimens. The results indicated that the proposed model not only predicts the strong nonlinear behavior of plain and notched specimens, but also can estimate the failure strain with sufficient accuracy.